Protecting All : Risk Sharing for a Diverse and Diversifying World of Work - Packard, Truman; Gentilini, Ugo; Grosh, Margaret; O’Keefe, Philip; Palacios, Robert; Robalino, David; Santos, Indhira (Washington, DC: World Bank, 2019)
This white paper focusses on the policy interventions made to help people manage risk, uncertainty and the losses from events whose impacts are channeled primarily through the labor market. The objectives of the white paper are: to scrutinize the relevance and effects of prevailing risk-sharing policies in low- and middle-income countries; take account of how global drivers of disruption shape and diversify how people work; in light of this diversity, propose alternative risk-sharing policies, or ways to augment and improve current policies to be more relevant and responsive to peoples’ needs; and map a reasonable transition path from the current to an alternative policy approach that substantially extends protection to a greater portion of working people and their families. This white paper is a contribution to the broader, global discussion of the changing nature of work and how policy can shape its implications for the wellbeing of people.